(untitled) (Semiárida, 2018)
Pork production is positioned as an alternative for livestock farming that generates economic value adds, employment opportunities and social ties in communities of the hinterland regions. However, that activity must face a future scenario of great challenges driven by the macroeconomic and sectoral policies implemented in Argentina, since the end of 2015. The effects of those policies on the national evolution of pork productive and commercial variables are assessed, in this paper, by calculation of the economic output of primary feed production in La Pampa province. This involved the performing of a descriptive and regional investigation, which was instead worked out by modeling of typical production systems, calculation of economic results and comparison of costs and average incomes. In spite of the continuous increase in pork consumption, its upward trend in national production was slowed down. The growing gap between these two variables was covered up by imports, which increased sharply in relative terms. The profit margins for pork producers in La Pampa province were reduced, due to increments in costs that resulted proportionally greater than the observed for their income. This reveals a scenario where the economic result depends on the efficiency of production management, adoption of technologies, advances in associativity as an alternative to scale progress, improvements in the purchasing of supplies and access to new commercial channels.